Some preliminary evidence on the short-run aggregate demand effects of fiscal policy - Canlas, Dante B. (1986)
The crowding out of private consumption by fiscal policy is examined using a short-run consumption function. There is evidence of a one-for-one crowding out of consumption by government purchases of goods and services. The effects of debt financing on consumption are mixed. Internal debt exerts a negative effect while external debt, a positive one.
Keywords: Consumption (Economics); Fiscal policy; Public debts -- Philippines; External debts